Caregivers' Perceptions of Their Child's Language Disorder: Alignment between Caregivers and Speech–Language Pathologists - Selin, Jennifer; Hill, Margaret S.; Schmitt, Mary Beth (Seminars in Speech and Language, 2018)
Caregivers' perceptions regarding their child's language disorder may influence caregivers' involvement in therapy as well as daily home interactions, thus impacting developmental outcomes. However, little is known about the alignment between caregivers' perceptions of their child's language disorder and those of speech–language pathologists (SLPs), nor of factors that might relate to alignment between caregivers and SLPs. This study addressed three aims: (1) to characterize caregivers' perceptions regarding children's quality of communicative interactions, competence in communicative abilities, and outcomes of communicative improvement; (2) to measure alignment between caregivers' and SLPs' perceptions; and (3) to explore caregiver- and child-level factors that might relate to alignment. Caregivers and SLPs of 3- to 4-year-old children currently receiving treatment for language disorders completed questionnaires to assess perceptions along with two caregiver factors (maternal education and self-efficacy) and child language disorder severity. Caregivers' perceptions were more positive and more variable than those of SLPs. However, caregivers and SLPs agreed in rating perceptions of present and future outcomes higher than either quality or competence. Maternal education, caregiver's self-efficacy, and children's language disorder severity were not related to alignment between caregivers and SLPs. Given the variability in caregivers' perceptions, future research should explore the role of perceptions in children's language intervention outcomes.
Keywords: language disorders; preschool children; caregivers' perceptions